Women’s awareness of urinary incontinence - Juszczak, Katarzyna; Słomiana-Amjedullah, Tatiana; Koźlak, Violetta; Cebulska , Violetta (Nursing in the 21st Century, 2021)
WOMEN’S AWARENESS OF URINARY INCONTINENCE Introduction. Urinary incontinence consists in an involuntary leakage of urine from the urethra. It affects both women and men, but women get ill more often. Although the morbidity peak falls on perimenopausal age, urinary incontinence can occur at any age. The highest percentage of patients is the elderly population.Aim. Assessment of women’s awareness of urinary incontinence.Materiala and methods. The group of study participants comprised 130 women aged between 18 and 89. The tool used in the study was the authors’ own questionnaire. The questionnaire consists of 31 questions, including, among others, demographic questions about age, marital status, education, occupational situation, number of births, number of children as well as definitions, risk factors, prevention and treatment of urinary incontinence.Results. The women subjected to the study self-assessed their state of knowledge on urinary incontinence. The study showed that 37 people (28.5%) assessed their state of knowledge as good, 42 people (32.3%) as sufficient and 51 (39.2%) as insufficient. For 56.15% (n=73) of the surveyed women, the most common source of knowledge about urinary incontinence was non-professional literature (magazines and newspapers). The study showed a statistically significant relationship between knowledge of urinary incontinence and education (Chi square X2=24.472; p≤0.0004). People with higher education had a better knowledge about urinary incontinence.Conclusions. The level of knowledge of the research participants about urinary incontinence is insufficient. A sense of shame and lack of time are the main reasons for low reporting of the UI problem to the doctor or nurse. There is a need to run an educational campaign to make the public aware of treatment options and IU prevention.